PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BENAR SALAH BERANTAI (TRUE FALSE CHAIN) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA MAN 1 PEKANBARU - Jannah, Miftahul Jannah Miftahul; Amran, Elva Yasmi Amran Yasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The Research about application of the active learning strategy type true false chain has been done to improve studentâs achievement on the topic of solubility and solubility product constant in class XI IPA MAN 1 Pekanbaru. This research is experimental research based on pretest-posttest design. The samples of this research were the students of class Xl IPA 4 as the control class and students of class XI IPA 3 as the experimental class that randomly selected after testing homogeneity. Experimental class is a class that is applied active learning strategy type true false chain, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,80 > 1,67, means that the application of active learning strategy type true false chain can improve student achievement on the subject of solubility and solubility product constant in class XI Science SMAN 1 Kampar where the effect of an increase is 10,10%.Key Words : Active Learning Strategy Type True False Chain, Learning Achievement, and Solubility and Solubility Product Constant